Tratamento e reuso de água em abatedouro de suínos - Tavares, Adenir Paulo (2013)
The slaughter industries as well as the industrialization of food products consume in its production process a very high volume of drinking water, which, makes these industries seek ways to minimize as much as possible this high consumption, because the processes of slaughtering and industrialization of swine meat are generated every day thousands of cubic meters of wastewater that untreated become a serious environmental problem. But with proper treatment it's possible to reuse this treated effluent in various industrial processes, thereby reducing the use of treated water in processes where it is not necessary the utilization of drinking water, with it the solution proposed in this work is precisely to ruse the effluent of an abattoir porcine from Medianeira to reduce the amount of water withdrawn or purschased from the dealership and subsequently reduce the amount of effluent disposed in the receiving body.